The legal provisions regarding the trade name according to Law No. 23 of 2010 concerning Libyan commercial activity (مجلة أبحاث قانونية, 2024)
‏The study examines the legal provisions of the trade name according to the Legislative Regulation Law No. 23 of 2010 regarding Libyan commercial activities, highlighting its significance as the primary and fundamental element of a commercial establishment. Without this name, the establishment lacks distinctiveness and independence, merely blending in with other businesses. Furthermore, the trade name is a fundamental data point for registering any commercial activity in the commercial registry. Consequently, the research emphasizes the necessity of specific procedures for registering trade names within the legislative framework.
Keywords: trade name; commercial establishment; commercial registry